Maple syrup urine disease presenting as severe neonatal metabolic encephalopathy: a case report - S., Giridhar; L., Umadevi; M., Rathinasamy; J., Antony (International Journal of Contemporary Pediatrics, 2020)
We report a 17 day old boy, who developed progressive encephalopathy, after an apparent period of normalcy. Magnetic resonance imaging showed diffusion restriction in myelinated areas like, a pattern suggestive of maple syrup urine disease. Dried blood spots for tandem mass spectrometry and urine for gas chromatography mass spectrometry confirmed elevation and excretion of branched chain amino acids respectively. After peritoneal dialysis, baby improved but continued to have residual neurological deficit, in spite of MSUD-specialized diet. Molecular studies confirmed the diagnosis. This report highlights the need for early identification of these infants to optimize neurological outcomes.